Optimalisasi Manajemen Humas dalam Meningkatkan Kompetensi Guru dan Siswa melalui Kerja Sama Eksternal - Faozi, Ahmad; Bakhri, Syaiful (Universitas Islam Negeri Walisongo, 2024)
This research is motivated by the high unemployment rate of vocational high school graduates which is one of the main problems in the world of vocational education in Indonesia. This is inseparable from the incompatibility of graduate competencies with industry needs. In addition, cooperation with industry that is not optimal and the inequality in the number of cooperation between departments also worsens the situation. In this condition, competition between vocational schools has become increasingly difficult to force each school to continue to improve the quality of its education. This study uses a descriptive qualitative method with a case study approach. Data collection is carried out through interviews, observations, and documentation. After that, the data is analyzed by reducing, presenting, and drawing conclusions. The results of the first planning research set the goals of the cooperation to be carried out. Second, update information, make an MoU, and make a timeline for coordination meetings and report results. The implementation of public relations in building the first cooperation of public relations carries out cooperation with industry in an effort to improve teacher competence through training and student competence through street vendors and training. Second, public relations in updating information through offline and online. The three public relations agencies have implemented many MoUs, there are 18 MoUs carried out by public relations. Fourth, in the implementation of coordination meetings with school structures, they are carried out every Monday, while internal public relations meetings are held once a month. The first evaluation is to re-check that the cooperation carried out is in accordance with the vision and mission, the second in evaluating the update of public relations information involves departments to participate in evaluating. Third, the evaluation of the MoU is carried out when the cooperation period has expired, which is every two years. The four evaluation techniques used by public relations are two, namely oral techniques and written techniques. The impact of the collaboration with external parties is an increase in teacher competence through the internship program. Students benefit from Field Work Practice (PKL) programs that are relevant to industry needs. Further research could focus on the direct evaluation of the impact of cooperation with industry on job skills and the level of graduate absorption in the job market.